The hydrological regime of the Tigris River in the city of Baghdad (Journal of the College of Education for Women, 2019)
Water drainage pattern in the rivers and changed the nature of the renewed feeding areasin the basin in terms of topographic and geological conditions and climate in addition to thehuman role in organizing the process flow within these basins. This study addressed thedevelopment of the Tigris River Hydrological in the city of Baghdad and found that theannual rate of water drainage in the Tigris River was driven down very significantly,especially in the past twenty years, and since 1996 up to 2014 record flow rates of less thanthe overall rate of discharge of water, a (950 m3 / s ), in addition to the quarterly decrease thedischarge rates, especially since the beginning of the year 2000 and took converge all fourseasons rates within the (500 m3 / s). As is the drainage class (501-600 m3 / s) highercategories the disposal again for the discharge of daily Vtakerrt in ten years (2001-2010) Addto it has become water attributed to the River recorded rates within the (27 m) after it wasrecorded rates of between (28 - 30 m) in the nineties, and resulted in the discharge and thealleged lack of water and low water flow capacity of any reduction in the current speed of thewater of the Tigris River in the city of Baghdad to the low speed rates over the previous years.